Epigenetic upregulation of acid-sensing ion channel 1 contributes to gastric hypersensitivity in adult offspring rats with prenatal maternal stress. Issue 5 (May 2020) - Wang, Hong-Jun; Xu, Xue; Zhang, Ping-An; Li, Meng; Zhou, You-Lang; Xu, Yu-Cheng; Jiang, Xing-Hong; Xu, Guang-Yin
Abstract : Abstract: Functional dyspepsia is a common functional gastrointestinal disorder. Gastric hypersensitivity (GHS) is a hallmark of this disorder, but the cellular mechanisms remain largely unknown. Stressors during gestational period could have effects on the offspring's tissue structure and function, which may predispose to gastrointestinal diseases. The aim of this study was to test whether prenatal maternal stress (PMS) induces GHS and to investigate role of acid-sensing ion channel (ASIC)/nuclear factor-κB (NF-κB) signaling by examining Asic1 methylation status in adult offspring rats. Gastric hypersensitivity in response to gastric distension was examined by electromyography recordings. Changes in neuronal excitability were determined by whole-cell patch-clamp recording techniques. Demethylation of CpG islands of Asic1 was determined by methylation-specific PCR and bisulfite sequencing assay. Prenatal maternal stress produced GHS in adult offspring rats. Treatment with amiloride, an inhibitor of ASICs, significantly attenuated GHS and reversed hyperexcitability of gastric-specific dorsal root ganglion (DRG) neurons labeled by the dye DiI. Expression of ASIC1 and NF-κBp65 was markedly enhanced in T7 to T10 DRGs. Furthermore, PMS led to a significant demethylation of CpG islands in the Asic1 promoter. A chromatin immunoprecipitation assay showed that PMS also enhanced the ability of NF-κBp65 to bind the promoter of Asic1 gene. Blockade of NF-κB using lentiviral-p65shRNA reversed upregulation of ASIC1 expression, GHS, and the hyperexcitability of DRG neurons. These data suggest that upregulation of ASIC1 expression is attributed to Asic1 promoter DNA demethylation and NF-κB activation, and that the enhanced interaction of the Asic1 and NF-κBp65 contributes to GHS induced by PMS. Abstract : Prenatal maternal stress enhances Asic1 demethylation and interaction of NF-κBp65 with Asic1 promoter in dorsal root ganglion, leading to gastric hypersensitivity in adult offspring rats.